2017
DOI: 10.1155/2017/6237689
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Information Processing Strategy Training on Academic Task Performance in Children with Learning Disabilities: A Pilot Study

Abstract: Learning disabilities (LD) can be associated with problems in the four stages of information processing used in learning: input, throughput, output, and feedback. These problems affect the child's ability to learn and perform activities in daily life, especially during academic activities. This study is a pilot study aimed at investigating the effectiveness of information processing strategy training using a combination of two approaches that address the ability to apply processing strategies during academic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 12 publications
(27 reference statements)
2
10
0
Order By: Relevance
“…In addition, one of the parts of the problem-solving process in OPC is a generalization and the fourth quadrant of the 4QM also includes problem-solving and thinking strategies; therefore, it seems that the child achieves autonomy in one goal by generalization to other contexts. This seems to be in agreement with the findings of Juntorn et al and Jamali et al [ 35 , 63 ].…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…In addition, one of the parts of the problem-solving process in OPC is a generalization and the fourth quadrant of the 4QM also includes problem-solving and thinking strategies; therefore, it seems that the child achieves autonomy in one goal by generalization to other contexts. This seems to be in agreement with the findings of Juntorn et al and Jamali et al [ 35 , 63 ].…”
Section: Discussionsupporting
confidence: 94%
“…The development of specific skills required for occupational performance in our study was done using 4QM which confirms the study of Sohlberg et al about the effectiveness of the systematic instruction approach [36]. Furthermore, our results also support Juntorn et al's study which indicated that systematic prompts of 4QM were used to improve the ability of mothers to recall information about how to sequence steps needed for their child's goals [35]. Occupational therapists believe that for health and well-being as the core of the ICF-CY, there must be a balance in the occupational performance areas such as self-care, productivity, and leisure [64].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Thus, the therapist has the primary goal of making possible the recovery of the affected upper extremities [ 5 , 6 , 7 ]. Task-oriented training is a very beneficial therapy for upper extremity rehabilitation [ 8 , 9 , 10 ]. Intensive repeated training is also an essential therapy for nerve rehabilitation interventions as it can help nerve regeneration and upper extremity function enhancement [ 9 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%